2012
DOI: 10.3168/jds.2012-5710
|View full text |Cite
|
Sign up to set email alerts
|

Stability of free and encapsulated Lactobacillus acidophilus ATCC 4356 in yogurt and in an artificial human gastric digestion system

Abstract: The objective of this study was to determine the effect of encapsulation on survival of probiotic Lactobacillus acidophilus ATCC 4356 (ATCC 4356) in yogurt and during artificial gastric digestion. Strain ATCC 4356 was added to yogurt either encapsulated in calcium alginate or in free form (unencapsulated) at levels of 8.26 and 9.47 log cfu/g, respectively, and the influence of alginate capsules (1.5 to 2.5mm) on the sensorial characteristics of yogurts was investigated. The ATCC 4356 strain was introduced into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 29 publications
(54 reference statements)
6
43
1
Order By: Relevance
“…In our beverages the survival of bifidobacteria reached the same levels reported by Kailasapathy (2006) after cell microencapsulation, and was higher than that found by Antunes et al (2005) in a probiotic yogurt containing a B. longum strain and enriched with both whey protein concentrate and skim milk powder. It is possible to argue that the occurrence of fibers in WPF beverages helped the survival of bifidobacteria as demonstrated by Crittenden R.G.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…In our beverages the survival of bifidobacteria reached the same levels reported by Kailasapathy (2006) after cell microencapsulation, and was higher than that found by Antunes et al (2005) in a probiotic yogurt containing a B. longum strain and enriched with both whey protein concentrate and skim milk powder. It is possible to argue that the occurrence of fibers in WPF beverages helped the survival of bifidobacteria as demonstrated by Crittenden R.G.…”
Section: Resultssupporting
confidence: 76%
“…The worsening in sensory attributes was previously found in a yogurt containing microencapsulated bifidobacteria cells (Kailasapathy, 2006). The sensory scores registered for the WPF beverages including RS and fermented with the M115 strain could be partially attributed to the positive influence of RS in accordance with results of Kailasapathy (2006) suggested as positive effect of capsulant and filler materials (alginate and Hi-Maize TM Starch) in masking the grittiness (mouthfeel) of the yogurt fermented with bifidobacteria.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Two criteria are required for administered probiotic bacteria to exert their functions. Probiotics must be protected from the stress of an extremely acid environment in the stomach and enzymatic deactivation in the stomach and the small intestine (19, 20). For example, LGG can grow after incubation in simulated gastric contents with the pH range 3.0–7.0 for 4 hours, but LGG is unable to grow at pH < 3.0 (21).…”
Section: Introductionmentioning
confidence: 99%
“…The viable number of L. acidophilus ATCC 4356 in these polymer matrices (MCPA and AP) was above 10 7 that is > 7 log 10 cfu/g which is the required minimum concentration of probiotic therapy able to confer health benefit (Anal and Singh, 2007). Ortakci and Sert (2012) found that L. acidophilus ATCC 4356 count in alginate calcium microbeads was reduced by 0.25 log 10 cfu/g after 30 min in SGJ. A little more than 1 log 10 cfu/g of L. gasseri and less than 1 log 10 cfu/g of Bifidobacterium bifidum in alginate-chitosan capsules were lost after 120 min in artificial gastric juice (Chávarri et al (2010).…”
Section: Survival Of Free and Microencapsulated Lactobacillus Acidophmentioning
confidence: 90%